(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Variable speed drive applications in the industrial vicinity playing a vital role in nation development. The majority of the industries are engaged with AC induction machine drives due to easy, smooth and reliable drive operations for its various variable drive applications. Recent advances in power electronic technologies makes the efficient control schemes to obtain a smooth and reliable variable speed drives. Modular multilevel converter (MMC) technique plays a significant role in applications of high power rating such as HVDC. The application of these modular multilevel converter techniques now extended to various variable induction machine speed drive applications in industrial services due to its superior benefits of investment and life cycle cost. Modular multilevel converters designed in number of modules to obtain ripple and harmonic less voltage out puts of the induction machines. Different topologies and control strategies of modular multilevel converters are observed and employed by the various researchers elsewhere in the world. This paper presets a novel review on applications of modular multilevel converters used in different drive applications. Also, this paper presents a detail review on different topologies and control schemes used elsewhere in the world and made suggestion on application of efficient modular multilevel converter technique configuration to obtain effective performance of induction machine at different drive applications